2009
DOI: 10.1002/cncr.24719
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase 2 study of belotecan, a new camptothecin analog, and cisplatin for chemotherapy‐naive patients with extensive‐disease small cell lung cancer

Abstract: BACKGROUND:The objective of this study was to investigate the efficacy of belotecan, a new camptothecin analog, combined with cisplatin for the treatment of chemotherapy‐naive patients with extensive‐disease small cell lung cancer (ED SCLC).METHODS:Treatment consisted of belotecan 0.5 mg/m2 daily on Days 1 through 4 and cisplatin 60 mg/m2 on Day 1 of a 3‐week cycle for up to 6 cycles unless there was disease progression, unacceptable toxicity, or patient refusal. Response assessment was done every 2 cycles usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…However, we found a higher proportion of patients with ECOG PS 2 than the study by Noda et al (16 % vs. 8 %). Moreover, the RR in the present study was approximately 10 % lower than previous phase II trials enrolling a smaller number of patients [1618]. To date, Lim et al have reported the highest RR (73.8 %) with the use of the BP regimen [18].…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…However, we found a higher proportion of patients with ECOG PS 2 than the study by Noda et al (16 % vs. 8 %). Moreover, the RR in the present study was approximately 10 % lower than previous phase II trials enrolling a smaller number of patients [1618]. To date, Lim et al have reported the highest RR (73.8 %) with the use of the BP regimen [18].…”
Section: Discussioncontrasting
confidence: 61%
“…To date, Lim et al have reported the highest RR (73.8 %) with the use of the BP regimen [18]. Lee et al reported a median PFS of 6.9 months and a median OS of 19.2 months in patients receiving the BP regimen [16]. In the current study, the degree of the difference in the RR between the two treatment arms was higher in the PP population than the mITT population (18.0 % vs. 13.1 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,31,32 Recently, Lee et al reported that CKD-602 combined with cisplatin delivered excellent results in a multicenter phase II study for patients with small cell lung cancer. 33 The response rate was 70% [95% confidence interval (CI), 50.6-85.3%], the median progression-free survival was 6.9 months (95% CI, 6.3-7.5 months), and the overall survival was 19.2 months (95% CI, 13.3-25.2 months), and the regimen was associated with tolerable toxicity. Grade 3 and 4 adverse events included neutropenia in 23 of a total of 30 patients, thrombocytopenia in eight patients, febrile neutropenia in nine patients, nausea in three patients, and pneumonia in three patients.…”
Section: Discussionmentioning
confidence: 99%
“…13 Belotecan, alone or in combination with cisplatin, has demonstrated promising outcomes in some cancers. [14][15][16][17] In recurrent ovarian cancer, use of belotecan as a single agent resulted in a 21%-45% response rate, and using it in combination with cisplatin showed a 47%-69% response rate with acceptable toxicity. Despite these results, there have been no reports on the efficacy of combination treatments, including belotecan and carboplatin.…”
mentioning
confidence: 99%